Performance analysis of class E ZVS inverters under varying load conditions in APT transmitter units - Husin, Siti Huzaimah; Md Saat, Mohd Shakir; Yusop, Yusmarnita; Md Jamal, Norezmi (Human Resource Management Academic Research Society, 2024)
This paper presents the design and analysis of a Class E Zero Voltage Switching (ZVS) inverter used in a 2.0 W Acoustic Power Transfer (APT) transmitter unit. The Class E ZVS inverter is chosen for its high-efficiency performance as an AC supply input voltage for an air transducer in an efficient acoustic power transfer system. The performance of the inverter under varying load conditions; resistive and actual air transducer modeled using the Butterworth Van-Dyke (BVD) equivalent circuit is investigated. The inverter is precisely designed to operate at the resonant frequency of 39.8 kHz, corresponding to the 40 kHz air transducer. Experimental results demonstrate a DC-AC power conversion efficiency of 85.42% with a resistive load. This study provides insights into the behaviour of the Class E ZVS inverter under different load conditions and suggests enhancements to improve efficiency in future applications.